FlexiThink: Decision Making and Design Thinking through Cognitive Flexibility Learning with a Transformative Multicultural Education Approach in Elementary Schools - Kadek Yudiana; I Dewa Ayu Made Budhyani; I Wayan Kertih (Universitas Pendidikan Ganesha, 2025)
One of the essential skills to be developed among elementary school students is decision-making and design thinking. To enhance decision-making and design thinking skills, innovative learning is required—specifically, Cognitive Flexibility Learning with a Multicultural Education approach. Therefore, the urgency of this study lies in improving these skills to enable students to compete in the era of the Industrial Revolution 4.0. Cognitive flexibility is crucial as it helps students successfully adapt to changing conditions, remain resilient under pressure, and respond effectively to new situations. This study employs a research and development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection methods in this study include observation, interviews, questionnaires, and tests. The subject of this study is the instructional model, while the object of research includes the validity, practicality, and effectiveness of the model. The validity testing involved expert evaluators, while the practicality testing involved practitioners in elementary education (teachers and students). The results of the analysis showed a Sig. (2-tailed) value of 0.000 > 0.05, indicating a significant difference between pre- and post-implementation outcomes of the Cognitive Flexibility Learning model based on Multicultural Education. This approach enables students to view situations from multiple cultural perspectives, allowing them to think flexibly, understand diverse viewpoints, innovate creatively, and collaborate effectively in a global context. It thus prepares them to face future challenges with improved skillsets.